Crystal structure of bis(1,3-bis(diphenylphosphino)propane-κ2P,P′)silver(I) trifluorosulfonate–methanol (1:0.5), [Ag(C27H26P2)]SO3CF3⋅0.5CH3OH - Yu Xiao; Li Yue-Xue; Lin Sen; Cui Yang-Zhe; Jin Qiong-Hua (Zeitschrift für Kristallographie - New Crystal Structures, 2017)
C55.50H54AgF3O3.50P4S, triclinic, P1̅ (no. 2), a = 11.7859(10) Å, b = 12.8900(11) Å, c = 18.8971(17) Å, α = 109.742(2)°, β = 92.891(1)°, γ = 100.998(1)°, V = 2631.9(4) Å3, Z = 2, Rgt(F) = 0.0405, wRref(F2) = 0.1129, T = 298(2) K.